Fracture of Nano and Engineering Materials and Structures Proceedings of the 16th European Conference of Fracture, Alexandroupolis, Greece, July 3-7, 2006 - Gdoutos, E.E.; Gdoutos, E.E. (Springer Netherlands : Imprint: Springer, 2006)
This volume contains two-page abstracts of the 698 papers presented at the “16th European Conference of Fracture,” (ECF16) held in Alexandroupolis, Greece, July 3-7, 2006. The accompanying CD attached at the back cover of the book contains the full length papers. The abstracts of the fifteen plenary lectures are included in the beginning of the book. The remaining 683 abstracts are arranged in 25 tracks and 35 special symposia/sessions with 303 and 380 abstracts, respectively. The papers of the tracks have been contributed from open call, while the papers of the symposia/sessions have been solicited by the respective organizers. Both tracks and symposia/sessions fall into two categories, namely, fracture of nanomaterials and structures and engineering materials and structures with 88 and 595 papers, respectively. Started in 1976, the European Conference of Fracture (ECF) takes place every two years in a European country. Its scope is to promote world-wide cooperation among scientists and engineers concerned with fracture and fatigue of solids. ECF16 was under the auspices of the European Structural Integrity Society (ESIS) and was sponsored by the American Society of Testing and Materials, the British Society for Stain Measurement, the Society of Experimental Mechanics, the Italian Society for Experimental Mechanics, and the Japanese Society of Mechanical Engineers. ECF16 focused in all aspects of structural integrity with the objective of improving the safety and performance of engineering structures, components, systems and their associated materials.